Busting Some of the Public Private Partnership Myths from a Government Perspective. Issue 3 (September 2017) - Curtain, Kim; Betts, Jim
Abstract: Since the 1980s, state governments across Australia have procured critical and complex infrastructure projects via a Public Private Partnership ("PPP"). Despite the long history and widespread use of PPPs in many sectors, there are still many misconceptions and myths regarding PPPs. This article attempts to demystify, from a government's perspective, some of those common misconceptions and myths. We noted that there are multiple ways of structuring a PPP arrangement, that the purpose is not to maximise risk transfer to the private sector but to allocate risks to the party best able to manage them and that a PPP structure does not circumvent funding constraints.